The Analysis of Practices of the Emerald Paradigm as a Way of Increasing the Effectiveness of Management Decisions - R. R. Veynberg; O. V. Litvishko; S. M. Sakharova (Вестник Российского экономического университета имени Г. В. Плеханова)
This article is devoted to an attempt to look at the problems of public administration of the Russian Federation from a different, evolutionary angle. Drawing a parallel between the level of development of society as a whole and the individual with the level of complexity of the structure of companies and the state apparatus, the main evolutionary turns were considered. Each such stage is different from the previous with the style of management in the organization, the complexity of hierarchical structures, requirements and expectations for employees of different ranks, corporate culture. Each organizational paradigm appeared in response to the external environment, stimulating adaptation to the changing reality in one way or another. The diversity and constant evolution of forms of relationships among individuals, organization of the process of their common work and is itself the proof, the cause and the necessity of continuous development of organizational structures. Each stage described in this paper has an existing analog - an organization that consistently operates on the basis of a particular paradigm. Among other things, the most modern forms of organizational structure - the so-called green and emerald organizations were studied: their strengths and weaknesses, the most interesting practices were analyzed. Based on the analysis of companies belonging to different paradigms, conclusions were made about the effectiveness of their practices to solve the fundamental problems of the state organization. Thus, having explained the reasons for the fundamental problems of the present state administration and having identified on the basis of which paradigm the state structures of the Russian Federation operate, the variants of their solution with the use of the experience of the so-called "orange", "green" and "emerald" organizations were proposed. According to the conclusions described in the article, it is impossible to move to a higher level of development by jumping a step or two, and therefore, at the moment it makes sense to consistently introduce selected practices of higher levels of development, carefully analyze the results of their implementation and, by trial and mistakes, to seek their own path of development.